A Rare Presentation of Giant Congenital Melanocytic Nevus: A Case Report - Hidayat, Dinnisa Haura Zhafira; Muhammad, Fathiyah Zahra; Ramadhani, Alyaa Syifa; Fariko, Kensha Firstyputri; Hanifah, Shabrina; Azmi, Valiant Zahirul; Budiarto, Bambang (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Giant congenital melanocytic nevus (GCMN) is a rare condition present at birth, with an estimated incidence of fewer than 1 in 20,000 live births. While smaller congenital melanocytic nevi are common, GCMN poses significant clinical concerns due to its potential malignant transformation into melanoma. Early recognition and long-term monitoring are crucial to mitigate risks. Objective: This case report aims to highlight the clinical presentation, diagnostic approach, and management challenges of GCMN to emphasize the importance of timely intervention. Case Presentation: A 24-year-old male presented with a progressively enlarging blackish facial lump that bled upon scratching. Laboratory tests indicated leukocytosis, and histopathology confirmed tumor growth in the epidermis with papillomatous architecture and hyperkeratosis, leading to a diagnosis of GCMN in the fronto-nasal region. Result: The histopathological findings confirmed GCMN, underscoring the need to its malignant potential. Despite its benign appearance, the lesion’s progressive growth and bleeding tendency warranted close monitoring. Conclusion: GCMN, though rare, requires early detection, appropriate treatment, and lifelong surveillance to prevent malignant transformation. Delayed intervention, often due to cosmetic concerns, may increase complications. Thus, a multidisciplinary approach involving regular follow-ups is essential for optimal patient outcomes.